2021
DOI: 10.3390/biomedicines9040344
|View full text |Cite
|
Sign up to set email alerts
|

Combined Proteotranscriptomic-Based Strategy to Discover Novel Antimicrobial Peptides from Cone Snails

Abstract: Despite their impressive diversity and already broad therapeutic applications, cone snail venoms have received less attention as a natural source in the investigation of antimicrobial peptides than other venomous animals such as scorpions, spiders, or snakes. Cone snails are among the largest genera (Conus sp.) of marine invertebrates, with more than seven hundred species described to date. These predatory mollusks use their sophisticated venom apparatus to capture prey or defend themselves. In-depth studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Ponericins, peptides from the Ponerine ant, have structural similarity with well-known antimicrobial and antibiofilm peptide cecropins [43]. While no known antimicrobial activity has been listed for the histamine releasing peptide from the oriental hornet, studies are ongoing for alpha-conotoxin obtained from cone snails, mainly used in pain management, to establish its antimicrobial activity [44]. An analog, ω -conotoxin MVIIA shows the peptide is effective against Candida kefyr and Candida tropicalis with moderate MIC values between 28–40 μM but it was not effective against any bacterial assay up to 500 μM [45].…”
Section: Resultsmentioning
confidence: 99%
“…Ponericins, peptides from the Ponerine ant, have structural similarity with well-known antimicrobial and antibiofilm peptide cecropins [43]. While no known antimicrobial activity has been listed for the histamine releasing peptide from the oriental hornet, studies are ongoing for alpha-conotoxin obtained from cone snails, mainly used in pain management, to establish its antimicrobial activity [44]. An analog, ω -conotoxin MVIIA shows the peptide is effective against Candida kefyr and Candida tropicalis with moderate MIC values between 28–40 μM but it was not effective against any bacterial assay up to 500 μM [45].…”
Section: Resultsmentioning
confidence: 99%
“…Ponericins, peptides from the Ponerine ant, have structural similarity with well-known antimicrobial and antibiofilm peptide cecropins (Orivel et al, 2001). While no known antimicrobial activity has been listed for the histamine releasing peptide from the oriental hornet, studies are ongoing for alpha-conotoxin obtained from cone snails, mainly used in pain management, to establish its antimicrobial activity (Ebou et al, 2021). An analog, ω-conotoxin MVIIA shows the peptide is effective against Candida kefyr and Candida tropicalis with moderate MIC values between 28 and 40 µM but it was not effective against any bacterial assay up to 500 µM (Hemu and Tam, 2017).…”
Section: Prediction Of Activity In Novel Antibiofilm Peptidesmentioning
confidence: 99%
“…With the wide application of AMPs in immunity and disease resistance, it is necessary to identify AMPs quickly and efficiently. High-throughput prediction of AMPs from genome and transcriptome datasets is one of the practical effective methods for discovery of novel AMPs sequences (Amaral et al, 2012;Houyvet et al, 2018;Ebou et al, 2021). By employing multi-omics analysis, we were able to obtain sequences of those potential AMP-derived genes, and further to illustrate their expression patterns in different individuals and various tissues of the same Conus species.…”
Section: Multi-omics Datasets Are Valuable For Identification and Con...mentioning
confidence: 99%
“…The complex multi-component venom contains various bioactive peptides including AMPs, which have been identified in diverse toxic animals such as spiders, snakes, scorpions and bees for promising therapeutic drug developments (de Barros et al, 2019;Tang et al, 2020;Khalil et al, 2021;Tawfik et al, 2021). AMPs in cone snails seem to be less attentional (Yang et al, 2001;Periyasamy et al, 2012;De León-Nava et al, 2016;Bernaĺdez-Sarabia et al, 2019;Younis et al, 2019;Ebou et al, 2021) compared to other animals. A previous study reported that a O1-superfamily conotoxin extracted from Californian cone (Californiconus californicus) venom can inhibit the growth of bacteria Mycobacterium tuberculosis (Bernaĺdez-Sarabia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation